Association between Daily Tea Consumption and Sleep Quality: A Cross-sectional Analytical Study - Gabriella Beatrice; Tasya Meidy Pradhana; Yusak Mangara Tua Siahaan (Universitas Pelita Harapan, 2025)
Background: Sleep quality is a critical determinant of physical and mental health, and dietary factors such as caffeine intake from tea may influence sleep patterns. Evidence on this association in the Indonesian population remains limited despite the high prevalence of both tea consumption and poor sleep quality. This study aimed to investigate the relationship between daily tea consumption and sleep quality among Indonesian adults. Methods: A cross-sectional correlational study was conducted from January to March 2022 using an online survey. A total of 104 adults aged 18–64 years with low stress levels (Perceived Stress Scale score ≤13) were included. Tea consumption was assessed by frequency and quantity (cups/day), while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). A global PSQI score >5 indicated poor sleep quality. Data were analyzed using Spearman’s rank correlation, with significance set at p < 0.05. Results: Most participants were female (61.5%), aged 20–49 years, with 40.4% consuming ≥3 cups of tea daily. Poor sleep quality was reported by 72.1% of respondents. A significant positive correlation was found between daily tea consumption and PSQI score (rₛ= 0.528, p < 0.001), indicating that higher tea intake was moderately associated with poorer sleep quality. Conclusions: Higher daily tea consumption is significantly associated with poorer sleep quality among Indonesian adults. These findings underscore the need for public health initiatives to raise awareness about caffeine-containing beverages and their potential effects on sleep.